Eugenol-induced suppression of biofilm-forming genes in Streptococcus mutans: An approach to inhibit biofilms. Issue 4 (December 2014) - Adil, Mohd; Singh, Kunal; Verma, Praveen K.; Khan, Asad U.
Abstract: Streptococcus mutans is well documented as a major aetiological agent of dental caries. The ability to form a biofilm on tooth surfaces is the major virulence factor of this bacterium. The objective of this study was to evaluate the effect of eugenol on suppression of biofilm- and quorum sensing (QS)-related genes of S. mutans and to determine its putative mode of action. Eugenol was evaluated for its inhibitory activity against virulence properties such as adherence and biofilm formation. Morphological changes in the architecture of S. mutans and in the biofilm were analysed and observed using confocal laser scanning microscopy and transmission electron microscopy. The effects of eugenol on expression of biofilm- and QS-related genes (gtfB, gtfC, comDE, smu630, vicR, brpA, ftf, relA, gbpB and spaP) were checked by quantitative real-time PCR (qRT-PCR). The present data revealed that eugenol at a sub-minimum inhibitory concentration (sub-MIC) significantly downregulated the expression of tested genes but did not affect bacterial growth. These results suggest that a sub-MIC of eugenol can effectively suppress virulence genes. Thus, the results indicated that eugenol can inhibit caries-associated biofilm and showed its therapeutic potential against oral biofilm.